Comparison of teaching and learning practices among teachers of the national and cluster secondary schools in Malaysia - Ismail, Habsah; Konting, Mohd Majid; Wan Ali, Wan Zah; Hassan, Roshafiza (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This paper reports the study conducted on the issues of teaching and learning practices among teachers in the Cluster Secondary and the National Secondary Schools in Malaysia. A total of 24 items were used to measure the practices towards teaching and learning in the classrooms as perceived by teachers of these schools. Findings of the study show that the practices of Cluster Secondary School teachers towards teaching and learning is high with a mean of 3.997 and a standard deviation of 0.494 compared to teachers of the National Secondary School with a mean of 3.837 and a standard deviation of 0.507. Findings of the study in a five-point scale of this two school categories also show that there was a significant difference in the teaching and learning practices among National Secondary Schools teachers of different ages, but not their counterparts in Cluster Secondary Schools. Despite some differences, the results indicate that teachers from both types of schools have positive teaching and learning practices.